STUDI KARAKTERISTIK IMPELER PADA DIGITAL MULTIJET TURBINE FLOWMETER UNTUK KEPERLUAN TELEMETRI - , TRI SETIA PUTRA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Telemetry is a technology that allows measurements to be made at a distance, via radio wave or web network transmission and reception of the information. Sensors installed on the monitoring station to measure the physical quantities on a condition, results of the data in the form of electrical information that is reinforced by the amplifier system early (pre-Amp). The signal is then compare order to get a digital signal that will be used as input to the microcontroller. The input signal comes a Hall Effect sensor is used to determine the number of rotation on the flowmeter impeller, because the rotation is proportional to the amount of flow rates. Data measurement results are then displayed on the LCD and telemetry sent via GSM Network. This study discusses the influence of variation of the impeller flow measurement and telemetry. Divide into 12 specimens this study also aims to determine whether the characteristics of the impeller at different measuring tools will give different measurement results. From testing on each specimen obtained a test specimen to be used for further testing, validation testing of measuring instruments, gauges the performance testing, and testing of telemetry. The results showed that the measurement is much better when using a series of signal conditioners. At the same impeller rotation, the greater number of blades or the greater diameter of the hub then the flow rate that flows gets smaller. The value of k meter factors at each measuring instrument can be different depending on the type of measuring instrument that is in use. By using a flowmeter made in this study, the flowmeter can perform the best readings when using impeller specimen 1 (3 blades and Î± = 0.3). By using this system, telemetry measurement can be done well. Measurement is successful if the readings on the same gauge as the content of SMS messages received by users. The accuracy of the measuring tool that is made in this study reaches Â± 2.38% of full scale. Precision measuring instrument readings is Â± 20 mL. Resolution measurements of total flow that can be shown the smallest gauge that reaches 0.01 L.